A phase II study of neoadjuvant chemotherapy with S‐1 and cisplatin for stage III gastric cancer: KUGC03. Issue 1 (25th November 2015) - Okabe, Hiroshi; Hata, Hiroaki; Ueda, Shugo; Zaima, Masazumi; Tokuka, Atsuo; Yoshimura, Tsunehiro; Ota, Shuichi; Kinjo, Yousuke; Yoshimura, Kenichi; Sakai, Yoshiharu; ,
Abstract : Objectives: A multi‐center phase II study was conducted to evaluate the safety and efficacy of neoadjuvant chemotherapy (NAC) with S‐1 plus cisplatin for advanced gastric cancer. Methods: The eligibility criteria were clinical T3/T4 or N2, not Stage IV. Patients received two 35‐day cycles of S‐1 plus cisplatin, and then underwent D2 gastrectomy. The primary endpoint was 3‐year progression free survival (PFS). Secondary endpoints were ratio of R0 resection, response rate, adverse events, and overall survival. A sample size of 49 was determined to have 80% power for detecting 15% improvement in the 3‐year PFS over 55% at a one‐sided alpha of 0.1. Results: Among 53 patients enrolled, 44 patients completed two cycles of NAC (83%), and 48 patients underwent R0 resection (91%). Postoperative complications occurred in 13 patients (26%). A pathological response was confirmed in 24 patients (45%), including four complete responses. The 3‐year PFS was 50.7%, while the 3‐year OS was 74.9%. Conclusions: Although the observed 3‐year PFS rate was worse than expected, NAC with S1 plus cisplatin was safe and led to a high rate of R0 resection. A randomized controlled trial is needed to make conclusions about the effectiveness of NAC in Japanese patients undergoing D2 resection. J. Surg. Oncol. 2016;113:36–41 . © 2015 Wiley Periodicals, Inc.